The Challenges of Cesarean Delivery at Teaching Hospital Gabriel Toure, Bamako Mali - Sissoko, Abdoulaye; Traore, Alassane; Kante, Ibrahim; Bocoum, Amadou; Traore, Soumana Oumar; Fane, Seydou; Dembele, Daniel; Kouma, Aminata; Sima, Mamadou; Tounkara, Fatoumata K.; Fomba, Amadou; Teguete, Ibrahima; et al. (Medical Science: Trends and Innovations Vol. 9, 2025)
Introduction: Cesarean permits to treat difficulties related to vaginal delivery and risk situations of fetal asphyxia. It also permits to save the mother and fetus. However, in developing countries as ours, complications related to this cesarean are not to be neglected. It constitutes an important cause of maternal and fetal morbidity and mortality. Here, the experience of the structure of complications of cesarean is reported. Objectives: The objectives of this study were to study the complications of cesarean section at the teaching hospital Gabriel TOURE, Bamako, Mali. Materials and Methods: A cross-sectional analytic study from January 1st 2003 to December 31st 2013 was carried out. All the patients who gave birth by cesarean operation in the gynecology-obstetric service of the teaching hospital Gabriel TOURE were included during this period of study. Descriptive statistics were used, Chi-square test, Pearson, and Cochran Armitage test have been used to calculate the P-value of trend. A multivariate analyses with a high alpha threshold of 10%, and then logistic regression multivariate was performed. It has been applied to appreciate the effect of maternal characteristics, obstetric practice, systemic factors, on the cesarean delivery rate and the complications. Results: We have registered 28,376 deliveries with 9509 cases of cesarean (33.5%) and a complication cesarean rate of 32% (3049/9509). The main risk factors for cesarean operation completions were adolescence, primiparity, obesity, the non-realization of antenatal care, evacuations and co-morbidities. Intraoperative complications were dominated by hemorrhage 8.3% and bladder lesion 1.1%, whereas anemia (58.8%) and parietal infection (21.1%) dominated the postoperative complications table. The evacuation (Odds Ratio adjusted (ORa) = 1.96) as well as pre-eclampsia/eclampsia (ORa = 2.34) and the sickle cell disease (ORa = 9.99) were the main influencing factors of maternal death. Praevia placenta (ORa = 1.75) abruption placenta (ORa = 11.08) and fetal malformation (ORa = 2.21) dominated the influencing factors of perinatal death. Conclusion: The cesarean complications rates were high in our improvement of the quality of antenatal care. The reorganization and revitalization of the reference and against reference system will permit the program some cesarean operations to reduce the morbidity related to cesarean.